2021
DOI: 10.3390/md19030126
|View full text |Cite
|
Sign up to set email alerts
|

Oceanapiside, a Marine Natural Product, Targets the Sphingolipid Pathway of Fluconazole-Resistant Candida glabrata

Abstract: Oceanapiside (OPS), a marine natural product with a novel bifunctional sphingolipid structure, is fungicidal against fluconazole-resistant Candida glabrata at 10 μg/mL (15.4 μM). The fungicidal effect was observed at 3 to 4 h after exposure to cells. Cytological and morphological studies revealed that OPS affects the budding patterns of treated yeast cells with a significant increase in the number of cells with single small buds. In addition, this budding morphology was found to be sensitive in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Confirm that your intended meaning is retained Confirm that your intended meaning is retained with a minimum inhibitory concentration (MIC) of 25 µg/mL, which is comparable to the activity of oceanalin A (MIC = 30 µg/mL) [4] when tested under similar conditions. Due to its similarity in the structure of oceanapiside as a α,ω-bipolar compound with sphingolipid units on the ends of the molecule, oceanalin B may target the sphingolipid pathway of C. glabrata as demonstrated by the mechanism of action of oceanapiside [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirm that your intended meaning is retained Confirm that your intended meaning is retained with a minimum inhibitory concentration (MIC) of 25 µg/mL, which is comparable to the activity of oceanalin A (MIC = 30 µg/mL) [4] when tested under similar conditions. Due to its similarity in the structure of oceanapiside as a α,ω-bipolar compound with sphingolipid units on the ends of the molecule, oceanalin B may target the sphingolipid pathway of C. glabrata as demonstrated by the mechanism of action of oceanapiside [11].…”
Section: Resultsmentioning
confidence: 99%
“…Some of these substances are glycosylated with a glucose or galactose residue [1][2][3][4][5][6]8]. α,ω-Bipolar sphingolipids substances exhibit antifungal [4,5,10,11], antimicrobial [1] and cytotoxic activity against mouse Ehrlich carcinoma cells [1]; DNAdamaging activity [6] and inhibition of protein kinase C activity [9]. In continuation of our search for new antifungal agents against the pathogenic fluconazole-resistant yeast Candida glabrata, we isolated oceanalin A (2) [4], a unique α,ω-bipolar compound containing isoquinoline and sphingolipid units on the ends of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the inhibition of polarized growth promoted by OPS is due to the disruption of organized actin. Phytosphingosine (PHS) was able to reverse OPS activity which indicates that it blocks fungal sphingolipid metabolism by specifically inhibiting the conversion step of PHS to phytoceramide [ 58 ]. Similarly, marine polyunsaturated fatty acids inhibit biofilm formation of C. albicans and Candida dubliniensis .…”
Section: Marine Compounds Potential Antimicrobial Activity and Curren...mentioning
confidence: 99%
“…Methylene blue dye (0.1 mg/mL in 0.1 M phosphate buffer with pH 7.2) was added to the cells and incubated for 5 min at RT. Five µL of the mixture was mounted onto a glass slide and was observed under a microscope [34]. According to yeast budding patterns, the cells were classified and counted, namely unbudded cells, cells with a single small bud, cells with a single medium sized-bud, and cells with a single large bud [35].…”
Section: Yeast Viability Assay With Methylene Bluementioning
confidence: 99%
“…A budding yeast experiment using methylene blue dye was performed to determine which cell cycle stage is targeted by B. asiatica seed extract. Methylene blue is a basic dye that can only penetrate nonviable cells producing blue fluorescence, while the absence of the blue coloration indicates viable cell [34]. The results showed that B. asiatica seed extracts caused a high accumulation of single dead cells at 84.3%…”
Section: Cell Cycle Arrest Assay Using S Cerevisiaementioning
confidence: 99%